Filogenia, biogeografia e diversificação de cactos na América do Sul com enfoque na tribo Cereeae (Cactaceae) - Romeiro-Brito, Monique (2023)
The global expansion of arid and semiarid habitats is often associated with climate changes that occurred during the Miocene and Pleistocene. Despite the relevance of these climatic events for the diversification of plants in xeric (dry) environments, few studies have been conducted related to the role of the expansion of aridity as a mechanism of diversification in South America. Besides the expansion of aridity, biotic factors may be involved with the diversification of taxon associated with xeric habitats, as observed in previous studies within the Cactaceae family. Due to the recent diversification of this family, molecular phylogenies that used few molecular markers have faced difficulties to distinguish the relationship within its main clades. A reasonable strategy to obtain higher accuracy and resolution in phylogenetic inferences is to employ genomic data combined with coalescence phylogenetic approaches. The present study aims to investigate biotic and abiotic factors associated with the diversification of tribe Cereeae, one of the major lineage of cacti in South America, and identify evolutionary and ecological patterns in common with taxa inhabiting xeric environments in South America. For this purpose, the following specific aims were established: identify ortholog genic regions available for Cactaceae and build a lineage-specific panel for shallow and deep-phylogenetic studies in this group using target capture sequencing approach (Chapter1); reconstruct a robust phylogeny for the tribe Cereeae, a group comprising the major diversity of Cactaceae in South America, using target capture sequencing approach. This phylogeny would be useful to delimitate well-supported suprageneric and generic relationships, and guide new taxonomic treatments (Chapter 2); and estimate divergence time and biogeographic events involved in the diversification of tribe Cereeae, as well as estimate shifts in diversification rates related to biotic and abiotic traits (Chapter 3). In brief, we selected more than five hundred ortholog nuclear regions and built a RNA bait panel, named here as Cactaceae591. As shown in chapter 1, these regions were capable of establishing phylogenetic relationships at deeper and shallower levels in Cactaceae. In chapter 2, we used newly generated target capture sequencing data and public databases to obtain a comprehensive view of phylogenetic relationships within the tribe Cereeae. The genomic dataset showed to be fundamental to obtaining highly supported phylogenetic relationships in this group, being the base to delimit suprageneric and generic groupings in this tribe. Finally, in chapter 3, we recovered that the divergence time estimated in tribe Cereeae is congruent with the period of expansion of aridity in Miocene and Pliocene. The group comprising globose cacti of subtribe Cereinae showed a shift in diversification rates during Pleistocene. The present study endorsesthe importance of morphological and ecological characteristics for the diversification of taxa inhabiting dry areas in South America.